The Effect of Knowledge Management Ability on Organizational Performance with Organizational Trust as A Mediation Variables - Fitria, Anikotul (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the effect of Knowledge Management Ability on Organizational Performance with Organizational Trust as a Mediation Variable in the Presto Milkfish Micro, Small and Medium Enterprises (MSMEs) in the city of Semarang. The population in this study was 117 MSME managers. The variables in this study were Knowledge Management, Organizational Performance, Organizational Trust. The method of data analysis used descriptive analysis and path analysis using SPSS version 21 software. The results showed that Knowledge Management and Organizational trust had an effect on Organizational Performance. Knowledge Management affects Organizational Trust. Furthermore ,. Organizational Trust is able to mediate the influence of Knowledge Management on organizational performance. Suggestions for future research are expected to test knowledge management variables with different dimensions such as knowledge sharing and organizational support. From the results of this research, it is hoped that the managerial Umkm will pay more attention to knowledge management and organizational trust in order to achieve optimal organizational goals. To improve knowledge management skills, management needs to attend training and seminars held by the government and other private parties